THE FUNDAMENTAL RIGHT ABOUT FREEDOM OF EXPRESSION AND PRESS AND THE RIGHTS OF PERSONALITY: AN ANALYSIS OF THE DECISION TO REMOVE REPORTS FROM THE CRUSOÉ MAGAZINE WEBSITES AND THE ANTAGONIST IN THE SUPREMO TRIBUNAL FEDERAL INQUIRY NO. 4781 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work has as its central theme the fundamental rights regarding the right to freedom of expression and journalistic information and their affectation to personality rights, having as its main objective the analysis of the clash between the mentioned principles, in order to verify which of the two should prevail in the case to be analyzed. For this purpose, a case study on the remove of reports from the Crusoé and O Antagonista websites had been proposed by Minister Alexandre de Moraes, a case that permeates the Inquiry No. 4781 of the Federal Supreme Court. The research used the hypothetical-deductive approach based on the exploratory type and through the collection of data in bibliographic sources available in physical media and in the computer network, in addition to the current Brazilian legislation and the analysis of the concrete case. The result obtained with the research was that the most adequate solution wasn’t used in the concrete case, since the decision wasn’t proportional, because when there’s a conflict between the right to freedom of expression and personality rights, it’s necessary analyze the concrete case by weighing the rights and assets, in order to fulfill the trinomial of Robert Alexy's (2017) theory of proportionality, which is necessity, adequacy and proportionality in the strict sense, allowing the use of less burdensome means such as the right of reply and indemnity, avoiding the censorship that is the most constrictive measure and that evokes sad episodes of Brazilian history.